If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + -2(b + -5) = 4 + 2b Reorder the terms: 3b + -2(-5 + b) = 4 + 2b 3b + (-5 * -2 + b * -2) = 4 + 2b 3b + (10 + -2b) = 4 + 2b Reorder the terms: 10 + 3b + -2b = 4 + 2b Combine like terms: 3b + -2b = 1b 10 + 1b = 4 + 2b Solving 10 + 1b = 4 + 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. 10 + 1b + -2b = 4 + 2b + -2b Combine like terms: 1b + -2b = -1b 10 + -1b = 4 + 2b + -2b Combine like terms: 2b + -2b = 0 10 + -1b = 4 + 0 10 + -1b = 4 Add '-10' to each side of the equation. 10 + -10 + -1b = 4 + -10 Combine like terms: 10 + -10 = 0 0 + -1b = 4 + -10 -1b = 4 + -10 Combine like terms: 4 + -10 = -6 -1b = -6 Divide each side by '-1'. b = 6 Simplifying b = 6
| 6n^4+20n^3+14n^2=0 | | y(x-7)-3(x-7)= | | 0.12x+3-0.8x=0.22-0.6 | | y^4+3y^2-1=0 | | 2(4)-5y=11 | | -68x=-41 | | 9-(-21)+10= | | 5(-4.4)-27= | | 3=3-6z-4z | | 12x+3-80x=22-60 | | 8x-4x=-28 | | Y/6-2=2 | | 5y=25-15x | | 15y=25-5x | | 14/33*3/4= | | y+x+(15z)x=9 | | y=x^2+15z | | 2(7)-3(-2)= | | 5/6m=7/8 | | -1.3x=13 | | x/2=9.4 | | 7x=3x-6+2x | | 11x^2+8x+14=0 | | 75(x-2)+2x=50 | | 6x-30y=0 | | 6x+9x=15-19 | | z+62=3916000 | | 3w^2-13w-220=0 | | -2X-9=-X-5 | | 52=(4x+1) | | 4u-8+2(2u+2)=-4(u+5) | | 14X+98=8X+62 |